PENGEMBANGAN MODUL KESEHATAN REPRODUKSI BERBASIS POSITIVE YOUTH DEVELOPMENT FRAMEWORK PADA POSYANDU REMAJA - Bani Bacan Hacantya Yudanagara; Rahmad Aji Prasetya; Aphrodita Cahya Buwana; Putu Vidyastitha Wiguna (Universitas Mataram, 2023)
Risky sexual behavior is common among teenagers in Tosari, Pasuruan, and is caused by lack of access to reproductive health knowledge. Data from primary health care stated that 60% of mothers who had children under five married at too-young age of 15-19 years. However, Tosari has an active and routine Youth Integrated Health Post or Posyandu Remaja (PR). PR is a community-based youth health service that can potentially increase access to reproductive health services for youth around PR. During the development period, youth needs to prevent risks, including risky sexual behavior, as described in the Positive Youth Development (PYD) framework. Therefore, a reproductive health education modul was developed using the PYD framework. Modul was delivered to PR cadres and members in Tosari using modules compiled through literature studies and assessments from experts and stakeholders. After that, attitudes and knowledge were measured through pre-test and post-test. The results showed a significant change in knowledge and attitudes among participants after following the education program (p < 0.001, effect size 0.649). This module and educational model are expected to improve and help youths to face challenges during the development period so that risky sexual behavior can be avoided.